The Qur’an, Human Rights, and the Muslim World: Between Text and Context - Saliha Kanwal; Hamzah Hassan (Journal of Religion and Society, 2025)
The relationship between the Qur'an and contemporary human rights frameworks is a subject of profound scholarly and theological debate. While the Universal Declaration of Human Rights (UDHR) embodies secular, universal principles, the Qur'an offers a divine ethical foundation centered on justice (‘adl), dignity (karāmah), and equality. This article explores the tensions and convergences between Islamic scripture and modern rights discourse, emphasizing the Qur'an’s affirmation of universal human dignity (Qur'an 17:70), equality (49:13), and freedom of conscience (2:256). Nonetheless, the classical Islamic jurisprudence, which distinguishes between God-given rights (huqquq Allah) and human rights (huqquq al-ibad), tends to conflict with liberal rights model, especially on gender, religious and legal penalties. Contemporary Muslim scholars are divided: traditionalists uphold classical fiqh as immutable, while reformists advocate ijtihād (independent reasoning) and maqāṣid al-sharī'ah (higher objectives of law) to reconcile Islamic ethics with modern rights. The article highlights contextual reinterpretation, feminist Qur'anic exegesis, and socio-historical analysis as tools to bridge gaps between text and context. Case studies of the Muslim-majority states indicate inconsistent rights practices that are determined by ideological conflicts between authenticity and modernity. The conclusion presents the argument in favor of the pluralistic discourse that would not subordinate Islamic moral autonomy to universal rights standards but would treat them critically, opposing both cultural relativism and hegemonic universalism. By centering the Qur'an’s ethical spirit over rigid legalism, the article envisions a transformative Islamic contribution to global human rights. Keywords: Qur'an, Human Rights, Islamic Law, Maqāṣid Al-Sharī'ah, Ijtihād, Gender Equality, Religious Freedom, Universalism, Contextual Interpretation, Muslim Reformism